Effect of Geometry and Number of Seismic Stations on Micro-Earthquake (MEQ) Hypocenters in Geothermal Fields - Utama, Widya; Garini, Sherly Ardhya; Hutapea, Merry C.; Putra, Dhea Pratama Novian; Warnana, Dwa Desa; Lestari, Wien (Postgraduate, University of Mataram, 2023)
Micro-earthquake (MEQ) distribution describes subsurface conditions that can contribute to monitoring the dynamics of geothermal reservoirs. Thus, the distribution of MEQ hypocenter locations with high accuracy becomes extremely important. Experiments were conducted with 3 variations of geometry and number of seismic stations, while Geiger and Coupled Velocity-Hypocenter methods were used to determine the location of MEQ. Experimental results show that in determining the location of the MEQ, the geometry and number of seismic stations played an important role. Increasing the number of stations with relatively long distances can result in less accurate locations of MEQ, error and bias in determining the location of MEQ will be greater when the azimuth gap value is greater. This is shown by the distribution of MEQ that are more spread out in variations 4A and 4B (4 seismic stations) compared to the distribution of MEQ hypocenters using data from 8 seismic stations. The azimuth gap variations of stations 4A and 4B are 283° and 267°, and 8 stations have a value of 222°. The large value of the azimuth gap is due to the distribution of stations only on one side so that there are horizontal angles that are not covered by seismic stations.